THE PELATIHAN MEMBUAT VIDEO PEMBELAJARAN MENGGUNAKAN SMARTPHONE MELALUI APLIKASI KINEMASTER BAGI GURU ABAD 21: PELATIHAN MEMBUAT VIDEO PEMBELAJARAN MENGGUNAKAN SMARTPHONE MELALUI APLIKASI KINEMASTER BAGI GURU ABAD 21 - Eva Oktaviana, M.Pd; Evayenny (CV. Multi Kreasi Media, 2022)
The development of science and technology is growing very rapidly, especially during the Covid-19 period which has had a tremendous impact on society, especially in the world of education. Technology has an important role in the world of education, especially teachers use technology as a media for teaching. As in Distance Learning (PJJ) or online, teachers are required to be able to use technology in teaching. However, the use of technology in teachers who has more 40 years old can't use technology literate. The author also observed at SDN Bintara III Bekasi, there are many teachers who have not been able to make learning videos through gadgets. There are 25 teachers and only 2 teachers are able to make learning videos. From this problem, STKIP Kusuma Negara lecturers with brisik project held a PKM that is training about how to make learning videos using smartphones through the KineMaster application. The purpose of this PKM is to train elementary school teachers to be able to create and use learning video media and to know applications that can be used and create an effective and fun learning process for their students. This activity was carried out at SDN Bintara III Bekasi. It took three days on September 2021, 24. The evaluation of PKM activity had shown that the participants felt very enthusiastic and could improve the teacher's ability to make learning videos using smartphones through the KineMaster application.